Hubungan Motivasi Perawat dengan Kinerja Perawat di Ruang Rawat Inap Kelas III Rumah Sakit Pertamina Bintang Amin - Yosi Adelta; M. Arifki Zainaro; Triyoso Triyoso (Universitas Malahayati Lampung, 2023)
ABSTRACT Performance is a world issue today. This happens as a consequence of the community's demands for the need for excellent service or high quality services that are inseparable from standards, because performance is measured based on standards. One method of assessing the performance of nurses is by looking at the standards of nursing care. individual work motivation that encourages the achievement of a nurse's performance. Motivation is something that encourages someone to behave in achieving a goal. To find out the relationship between nurse motivation and nurse performance in the Class III Inpatient Room at Pertamina Bintang Amin Hospital in 2022. This type of research uses quantitative, analytical survey research design with a cross sectional approach, the population and sample are nurses at Pertamina Bintang Amin Hospital as many as 38 respondents, the sampling technique uses purposive sampling, data analysis uses univariate and bivariate using chi square. Seen by 38 respondents, 13 respondents (34.2%) have good motivation, 10 respondents (26.3%) good nurse performance and 3 respondents (7.9%) poor nurse performance. nurses are not good as many as 25 respondents (65.8%) with good nurse performance as many as 9 respondents (23.7%) and nurse performance is not good as many as 16 respondents (42.1%). Most of the nurses' motivation is in poor category. Most of the nurses' performance is in poor category. The results of data analysis using the chi square test obtained p-value values that have a relationship between nurse motivation and nurse performance in the third class inpatient room at Pertamina Bintang Amin Hospital in the year 2022 Keywords: Nurse Motivation and Nurse Performance ABSTRAK Kinerja (performance) menjadi isu dunia saat ini. Hal tersebut terjadi sebagai konsekuensi tuntutan masyarakat terhadap kebutuhan akan pelayanan prima atau pelayanan yang bermutu tinggi yang tidak terpisahkan dari standar, karena kinerja diukur berdasarkan standar. Salah satu metode dalam menilai kinerja perawat yaitu dengan melihat standar asuhan keperawatan. motivasi kerja individu yang mendorong pencapaian kinerja seorang perawat. Motivasi merupakan suatu yang mendorong seseorang untuk bertingkah laku dalam mencapai suatu tujuan. Diketahui hubungan motivasi perawat dengan kinerja perawat di Ruang Rawat Inap Kelas III Rumah Sakit Pertamina Bintang Amin Tahun 2022. Jenis penelitian menggunakan kuantitatif, rancangan penelitian survey analitik dengan pendekatan cross sectional, Populasi dan sampel adalah perawat di Rumah Sakit Pertamina Bintang Amin sebanyak 38 responden, teknik sampling menggunakan purposive sampling, analisa data menggunakan univariat dan bivariat menggunakan chi square. Dilihat 38 responden, perawat yang memiliki motivasi baik sebanyak 13 responden (34,2%) dengan kinerja perawat baik sebanyak 10 responden (26,3%) dan kinerja perawat kurang baik sebanyak 3 responden (7,9%), sedangkan motivasi perawat kurang baik sebanyak 25 responden (65,8%) dengan kinerja perawat baik sebanyak 9 responden (23,7%) dan kinerja perawat kurang baik sebanyak 16 responden (42,1%). Sebagian besar motivasi perawat kategori kurang baik.Sebagian besar kinerja perawat dengan kategori kurang baik.Hasil analisa data menggunakan uji chi square didapat nilai p-value ada hubungan motivasi perawat dengan kinerja perawat di ruang rawat inap kelas III Rumah Sakit Pertamina Bintang Amin Tahun 2022 Kata Kunci: Motivasi Perawat dan Kinerja Perawat